The Efforts of Islamic Religious Education Teachers in Internalizing Students' Social Politics at TMII Roudlotul Qur'an Metro - Nisfah, Amirotun; Midahayati, Rina; Wijaya, Adi; Masuwd, Mowafg (International Journal on Advanced Science, Education, and Religion, 2025)
The learning of Islamic Religious Education (PAI) aims to nurture students who are devoted to Allah SWT, possess strong faith, exhibit commendable moral character, and have a sound understanding of Islamic teachings, particularly in relation to core principles and sources. The role of Islamic Religious Education teachers extends beyond merely imparting knowledge; it encompasses the transmission of values that shape students' behavior in alignment with Islamic teachings. This includes fostering an understanding of both personal and social piety—where personal piety pertains to individual worship, and social piety is reflected in empathetic and socially responsible behavior. This study employs a qualitative approach, utilizing primary and secondary data sources collected through observation, interviews, and documentation. Findings indicate that Islamic Religious Education teachers at Raudhotul Qur'an Middle School play a vital role in internalizing social virtues among students. This is achieved through a structured value internalization process, beginning with the Value Transformation Stage—utilizing advice, role modeling, and disciplinary methods—followed by the Value Transaction Stage, which includes demonstrations and further modeling. The outcomes highlight a positive impact, evidenced by enhanced social awareness, increased empathy, and improved communication skills among students at TMII Raudhotul Qur'an Middle School.